Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Cover cropping shifts microbial life-history strategies to promote necromass carbon accumulation through soil metabolite mediation in orchard systems - Yutao Zhang; Jia Liu; Kailou Liu; Daming Li; Rong Cui; Yaxin Liu; Xingjia Xiang; Ming Liu (Soil and Tillage Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Influence of multiple environmental factors on plastics in facility agriculture soils at a national scale, China - Guiming Liu; Sashuang Rong; Cun Liang; Yang Yang; Xuyang Zheng; Shutao Wang; Shiming Su; Zhenyong Li; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Unlocking synergy in thermophilic co-digestion of rice straw and food waste: boosting biogas production through accelerated kinetics and substrate biodegradability - Yaqian Liu; Ryoya Watanabe; Qian Li; Yutong Luo; Naohito Tsuzuki; Yu Qin; Rong Chen; Yu-You Li (Journal of Environmental Management, 2025)

Effects of soil labile carbon fractions and microbes on GHG emissions from flooding to drying in paddy fields - Yi Xiao; Rong Huang; Zongjin Zhang; Vanessa N.L. Wong; Xingyu Li; Xiaoyan Tang; Youlin Luo; Yingjie Wu; Jiang Liu; Shiwei Li; Changquan Wang; Bing Li (Journal of Environmental Sciences, 2025)

Discriminating the impact of soil moisture and vapor pressure deficit on vegetation greening over multiple time scales - Zijun Wang; Rong Wu; Jiazheng Li; Yangyang Liu; Chenfeng Cui; Junrong Liu (Global and Planetary Change, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Simulated analog crayfish meat based on 3D print: Effect of crayfish oil emulsion on gel properties of surimi - Xiaofeng Zhan; Shuhui Yang; Weixia Zhou; Yanyan Wang; Jianhua Rong; Youming Liu; Chuan Li; Yongqiang Zhao; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Multidimensional strategy for discovering saltiness-enhancing peptides in shrimp heads integrating ultra-high pressure hydrolysis and machine learning - Na Li; Yafang Song; Yang Liu; Rong Liu; Yahong Li; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Wood-derived self-standing carbon electrodes for electrocatalysis: design, performance, and prospects - Liu-Liu Shen; Xinkun Li; Peiran Wu; Jiansong Wang; Hui Yu; Yipu Xu; Yuhang Wang; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2025)

Design and synthesis of novel diamines for ultra low-temperature curable polyimides with enhanced copper adhesion - Jialin Tian; Xialei Lv; Wentao Wang; Jinhui Li; Jialin Zhang; Jie Liu; Chao Zhao; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2025)

Nanoengineered polymeric RNA nanoflowers for dual-pathway modulation and effective therapy for non-small cell lung cancer - Li Wang; Dongbin Guo; Yifei Shan; Luanbiao Sun; Rong Wang; Bingmei Wang; Jiyu Guan; Quan Liu; Runze Li; Changfeng Zhu; Yicheng Zhao (Chemical Engineering Journal, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Cholesterol and 24S-OHC Induce Neuronal Apoptosis and Necroptosis, but Not Ferroptosis Despite Elevated Iron Levels - Yinghui Li; Tingbin Xu; Jiahua Yang; Rong Liu; Yan Qu; Jun Wang (Molecular Neurobiology, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Erosion rates of yardang landforms downstream of the Peacock River, NW China - Bai Youliang; Bo Li; Jinhong Rong; Hui Chen; Jinming Zheng; Jianshe Liu; Tan Bao; Jiangnan Jin; Chuan Wang (Journal of Sedimentary Environments, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

Achnatherum inebrians tolerance to salt stress is linked with the changes of rhizosphere microbiome and root exudates - Ronggui Liu; Chao Wang; Jie Jin; Xiaoshan Zhu; Lanlan Chen; Yang Yang; Rong Zheng; Kamran Malik; Jianfeng Wang; Chunjie Li (Soil Ecology Letters, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Competitive exclusion of insect parasitic fungi: Enhanced metabolite biosynthesis in Beauveria bassiana and fatty acid production in Metarhizium robertsii during host coinfection - Kexin Liu; Gen Li; Siying Wu; Yang Zhang; Rong Zhou; Cheng Lv; Xingcheng Yue; Zhuoran Zhu; Tianzi Zhou; Bo Huang; Yulong Wang (Pesticide Biochemistry and Physiology, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Carbohydrate-metabolizing gastrointestinal bacteria mediate resistome divergence in high feed efficiency Holstein dairy calves - Tianyu Chen; Shangru Li; Jianxin Xiao; Rong Peng; Mo Sha; Jingjun Wang; Jiaying Ma; Wei Wang; Mei Ma; Shengli Li; Zhijun Cao; Shuai Liu (Journal of Hazardous Materials, 2025)

Hydrothermal carbonization: A potent strategy for simultaneously eliminating ARGs-associated pollutants in livestock manure and blocking ARGs horizontal gene transfer - Sunlin Chi; Jinmei Xiao; Jinying Xu; Aijing Li; Jianhui Hu; Xinyi Wang; Meiyan Zhang; Wei Liu; Yalan Zhang; Huijun Ding; Jun Rong; Li Leng; et al. (Journal of Hazardous Materials, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Development and validation of an LC-MS/MS method for a sensitive quantitation of livestock and poultry meat allergens - Shupeng Yang; Yingnan Shencheng; Yumeng Zhao; Meizhen Zhou; Mohamed F. Abdallah; Yanan Gao; Min Gao; Rong Zhang; Shuyan Liu; Yi Li (Food Chemistry, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Synergistic effects of pre-harvest drought and shade on flavor and aroma enhancement in fermented tea: Insights into JA/ABA signaling and metabolic regulation - Chenyu Shao; Xinyu Peng; You Li; Ziqi Chen; Xin Li; Rong Xu; Shuqi Qiu; Yuqi Luo; Jie Liu; Jianan Huang; Zhonghua Liu; Li Niu; et al. (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Anti-interference detection of Pb (II) in seawater enabled by a photo-electrostatic ZnFe2O4/MoS2 heterojunction electrode - Shu Huo; Rong Guo; Gengchen Li; Hong Liu; Wenbo Hang; Tingting Liu; Ye Ma; Minggang Zhao (Chemical Engineering Journal, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

Efficient strategy for fructose conversion to 2,5-furandicarboxylic acid, 2,5-dicarbonylfuran or 5-formyl-2-furancarboxylic acid over dual single-atomic Fe/Co catalyst - Maolin Li; Quanxi Lu; Zhichao Dong; Sijie Liu; Rong Tan (Chemical Engineering Journal, 2025)

Direct oxidation of trace methane to formaldehyde under ambient conditions by piezo-photocatalytic synergy - Qiyu Zhang; Li Rong; Yue Jiang; Zhiping Zhu; Xiaochang Lin; Yongzhen Ding; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2025)

Orbital-engineering-enabled electrified ferrocene–FeOOH membrane for effective flow-through organoarsenic mineralization and arsenic sequestration - Xin Gao; Qian Li; Rong Chen; Xuefeng Liu; Lin Yang; Yongshen Hou; Hao Sun; Yanbiao Liu; Haitao Wang; Yi Wang (Chemical Engineering Journal, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

ZxSAUR15 regulates root growth and abiotic stress tolerance: from genome-wide characterization of SAUR genes in Zygophyllum xanthoxylum to functional validation - Chunli Liu; Mengzhan Li; Yuting Yang; Rong Chai; Li Wei; Hongju Yin (Plant and Soil, 2025)

Bio-organic fertilizer amendment helps suppress tomato bacterial wilt disease by improving aggregation and enhancing the pathogen inhibition capacity within micro-aggregates - Menghui Dong; Eiko E. Kuramae; Mengli Zhao; Yi Min; Shanshan Liu; Xu Xu; Qirong Shen; Rong Li; George A. Kowalchuk (Biology and Fertility of Soils, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Decoupled motion planning method for 7-DOF manipulator and lifting joint in automated tomato harvesting - Jiacheng Rong; Yu Liu; Xianjun Li; Chao Gao; Pengbo Wang; Ting Yuan; Wei Li (Computers and Electronics in Agriculture, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

A sliding window method considering image shadow to detect Mars rock from MRO HiRISE datasets - Na Sun; Yongjiu Feng; Xiaohua Tong; Pengshuo Li; Rong Wang; Yuhao Wang; Yuze Cao; Zilong Cao; Xiong Xu; Yusheng Xu; Shijie Liu (Planetary and Space Science, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Carbon dots promote tomato growth and yield via photosynthesis enhancement and leaf senescence delay - Shuang Li; Wenbo Zhao; Wei Zhao; Zhen Jiao; Keqiao Cui; Rong Wang; Aiying Wang; Yuantao Tan; Huandong Li; Yue Yin; Feijuan Gao; Kaikai Liu; et al. (Journal of Plant Physiology, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

The application of manure and straw is beneficial for improving the content and stability of DOM in paddy soil - Qinghua Zhou; Jiayue Zhou; Weiliang Xiong; Shiwei Li; Ouping Deng; Yi Xiao; Xingyu Li; Bing Li; Changquan Wang; Xuesong Gao; Genchuan Bai; Jiang Liu; et al. (Journal of Environmental Management, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Community metagenomics, widely targeted metabolomics and volatilomics analysis reveal dynamic mechanism and correlation pattern in kombucha - Shiqi Li; Shuo Zhang; Rong Liu; Leran Wang; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Bioscience, 2025)

Effect of preheating-induced structural changes of mung bean starch and protein on the phase behavior, physicochemical properties, and digestibility of composite hydrogels - Yue Gu; Rong Xu; David Julian McClements; Tongxun Liu; Qingyun Li; Guowan Su; Mouming Zhao; Qiangzhong Zhao (Food Hydrocolloids, 2025)

Unraveling the source-terminal PAH pollution from coal chemical wastewater in the Yellow River Basin via molecular fingerprint concentration analysis - Rong Li; Quanzhen Liu; Xiong Xu; Yongchang Xie; Lihua Lin; Mengru Yang; Donghong Wang (Environmental Pollution, 2025)

Development and analysis of a forest fire emission inventory in China considering daily variation patterns - Rong Li; Jiaxin Liu; Mingda Zhang; Congwu Huang; Sihan Zhao; Meigen Zhang; Liangfu Chen (Environmental Pollution, 2025)

Meso–Cenozoic exhumation history of Northeast Asia and its connections with tectonic and climatic factors - Hongtao Wang; Shichao Li; Rong Yang; Xiaopeng Yang; Fangbin Liu; Zheren Zhao (Earth-Science Reviews, 2025)

Achieving high-concentration lignocellulosic sugars by using the Trichoderma reesei strain with high β-glucosidase activity for inducer synthesis and cellulase production - Kehang Li; Rong Li; Jiaxin Zhang; Hong Liu; Zhaoxian Xu; Mingjie Jin; Fengwu Bai; Yaohua Zhong (Chemical Engineering Journal, 2025)

One-pot strategy for multifunctional recyclable thermally conductive phase change composites toward efficient thermal management - Yunfang Li; Rong Zhang; Baokuan Zhou; Chenxi Liu; Xudong Fu; Hai Chen; Qingting Liu; Shengfei Hu (Chemical Engineering Journal, 2025)

Adipose-bone microenvironment precision-regulation nanoplatform: A visualized mild photothermal-enhanced osteogenesis strategy for osteonecrosis of the femoral head - Jinxuan Li; Mengting Gao; Yuhang Wang; Rong Dai; Qi Liu; Shutong Wu; Jian Zhang; Hua Wu; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2025)

Silica-centered crosslinking solid polymer electrolyte for sodium metal batteries - Jinfang Zhang; Rong Liu; Kexin Zhu; Wanyang Guo; Panpan Li; Huaxin Guo; Xiaofeng Li; Qingbing Xia (Chemical Engineering Journal, 2025)

Biochar-induced quorum sensing enhances methane production by strengthening direct interspecies electron transfer - Yu Li; Chenlong Fan; Lingsen Liu; Xuanyu Zhai; Bei Zang; Yu-You Li; Rong Chen (Bioresource Technology, 2025)

Characterization of the Complexity of Pore Structure in Coal and Its Relationship with Gas Desorption - Zhenyang Wang; Jiaxuan Liu; Shuhan Li; Liang Wang; Guanhua Ni; Congmeng Hao; Rong Zhang (Natural Resources Research, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Elucidation of the anti-fibrotic diseases mechanism of chelerythrine by integrative approach of network pharmacology and experimental verification - Wei Han; Gui-yun Qian; Qin-rong Wang; Jie Liu; Yong-ping Zhang; Jian Xu; Tingting Li; Zhe Li (Natural Product Research, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

3-hydroxykynurenine increase in kynurenine pathway driven bisphenol F induced anxiety- and depression-like behaviors - Yuxin Lin; Luyao Wang; Sining Meng; Jianjia Liu; Xinyu Li; Wenjuan Wang; Miaoyang Hu; Xi Wang; Weixia Duan; Shangcheng Xu; Jun Wang; Rong Gao (Science of The Total Environment, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Temporal-spatially metabolic reprogramming rewires the landscape of H3K27 acetylation to enable the initiation of liver regeneration - Qi Zheng; Xiaojiaoyang Li; Fanghong Li; Zhenyu Xu; Yajie Cai; Changmeng Li; Xiaoyong Xue; Shuo Li; Rong Sun; Guifang Fan; Jianzhi Wu; Jiaorong Qu; et al. (Science Bulletin, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Consortia of SQR9 mutant strains containing the luxS gene mutation can maintain higher functional stability than the wild type - Jingjing WANG; Lingxue MENG; Ying ZENG; Xinrui ZHU; Chuanyong TANG; Zhihui XU; Hongjun LIU; Rong LI; Qirong SHEN (Pedosphere, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Personnel exposure studies to multi-source diffusion of bioaerosols under biosafety laboratory - Level 2 plus operating conditions - Yongxin Wang; Zhijian Liu; Chuan Jiang; Lei Jiang; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Multifunctional microbial inoculation regulates compost product microbiomes, with implications for improving crop health and yield - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Xingxiang Deng; Guixian Xie; Gongwen Luo (Journal of Cleaner Production, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Strain-level diversity of Staphylococcus equorum impacts the quality characteristics and flavor profile of Qinling dry fermented sausages - Nan Zhang; Ruren Li; Liu Wu; Di Zhang; Futong Song; Wenqian Li; Yafang Yao; Liangyan Rong (Food Bioscience, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Nanoplastics under the charge effects: Unveiling the potential threats to amphibian (Rana nigromaculata) growth, intestinal damage and microbial ecology - Peng Fang; Shuzi Ye; Zidie Luo; Rong Guo; Yan Jiang; Lemei Liu; Siwen Li; Fang Xiao (Environmental Pollution, 2025)

Machine learning-driven discovery of efficient narrow-band green phosphor for wide-color-gamut backlight displays - Shuifu Liu; Kunjie Song; Shuxing Li; Rong-Jun Xie (Chemical Engineering Journal, 2025)

Dual-phased nickel sulfide heterojunction of Ni9S8/Ni3S2 doped with Co assembled on Ni foam as a highly efficient electrocatalyst for alkaline oxygen evolution reaction - Siqi Zhang; Chaonan Wang; Wenyi Peng; Jiahao Huang; Senkai Han; Siao Li; Rong Liu; Shulan Ma; Huiqin Yao (Chemical Engineering Journal, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Potential genetic characteristics of Bacillus velezensis LZUR632 enhance the resistance of Achnatherum inebrians to Cd stress by altering rhizosphere microbial community composition and functional genes - Jie Jin; Chao Wang; Ronggui Liu; Rong Zheng; Maohua Deng; Jianfeng Wang; Chunjie Li (Plant and Soil, 2025)

Correction to: Artesunate Protected Blood–Brain Barrier via Sphingosine 1 Phosphate Receptor 1/Phosphatidylinositol 3 Kinase Pathway After Subarachnoid Hemorrhage in Rats - Shilun Zuo; Hongfei Ge; Qiang Li; Xuan Zhang; Rong Hu; Shengli Hu; Xin Liu; John H. Zhang; Yujie Chen; Hua Feng (Molecular Neurobiology, 2025)

Integrative Approaches Identify Genetic Determinants of Levodopa Induced Dyskinesia - Ying Wan; Lu Rong; Qingyuan Li; Suzhi Liu; Wentao Li; Min Ye; Weifeng Luo; Anmu Xie; Jingsong Shao; Dengjun Guo; Xiaoping Zhang; Kezhong Zhang; et al. (Molecular Neurobiology, 2025)

The Reorganization of Subcortical Network Reflects Sensory-Motor Abilities in Patients after Spinal Cord Injury - Na Li; Meisi Song; Mao Pang; Xiaodan Ma; Weihong Qiu; Zhuang Kang; Yong Yu; Zhaocong Chen; Zulin Dou; Xiquan Hu; Bin Liu; Limin Rong (Brain Topography, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Optimal injection sites for therapeutic angiogenesis: HGF-mediated regulation of HIF-1α via MAPK/PI3K pathways in hypoxic endothelial cells - Peng Wang; Zhihua Rong; Fengshi Li; ShanShan Ma; Hongjuan Qiu; Wenzhuo Lian; Zongshu Li; Tianqi Chen; Qing Zhong; Wenjing Wang; Guoqiang Sun; ChangWei Liu; et al. (Tissue and Cell, 2025)

Corrigendum to “Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression” [Toxicology 514 (2025) 154129] - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Regulatory measures for mitigating physical and mental health impacts in aerospace environment: A systematic review - Rong Liang; Jing Gao; Xiaohui Liu; Xinyao Li; Haonan Chang; Rongdian Yang; Jiajia Yang; Dong Ming (Life Sciences in Space Research, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

The AP2/ERF transcription factor OfERF2 promotes flavonoid biosynthesis in Osmanthus fragrans - Xiangzhan Hai; Gege Liu; Miaomiao Lu; Rong Fan; Ke Li; Bingao Guo; Huijuan Zhang; Fude Shang; Yuanji Han (Tree Genetics & Genomes, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

Discovery of novel potential 11β-HSD1 inhibitors through combining deep learning, molecular modeling, and bio-evaluation - Xiaodie Chen; Liang Zou; Lu Zhang; Jiali Li; Rong Liu; Yueyue He; Mao Shu; Kuilong Huang (Molecular Diversity, 2025)

IFN-γ2 enhances proliferation and differentiation of muscle cells: a novel target of natural grass feeding mode improving muscle quality in grass carp (Ctenopharyngodon idella) - Huijie Chen; Yin Wang; Jieya Liu; Qiushi Yang; Jiamin Lu; Tingting Xu; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Source of dietary iron and zinc affects meat quality by altering muscular fatty acid profile, flavor substances, and metabolomics in finishing pigs - Zhimei Tian; Miao Yu; Yiyan Cui; Dun Deng; Min Song; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Meat Science, 2025)

Spatio-temporal dynamic characteristics of the substitution effect of ride-hailing travel and its multi-activity network: a case study of Chengdu - Zhicheng Zheng; Yang Li; Peijun Rong; Lijun Zhang; Yaochen Qin; Gangjun Liu (Journal of Transport Geography, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

Significant insights of CaO2 promoting heavy metal complexes removal during a plasma process - Meiqian Lu; Rong Li; Zichen Wang; Yue Liu; Guodong Zhang; Qiuling Ma; Jian Zhou; He Guo; Tiecheng Wang (Journal of Environmental Management, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Reductive dechlorination of 1,1,2-trichloroethane in groundwater by zero valent iron coupled with biostimulation under sulfate stress: Differences and potential mechanisms - Naijin Wu; Yi Li; Yizhou Liu; Yangfan Feng; Wenbo Fei; Tianwen Zheng; Liming Rong; Nan Luo; Yun Song; Wenxia Wei; Peizhong Li (Environmental Research, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

Plant and microbial β diversities are better predictors of ecosystem functioning than their α diversities, but aridity weakens these associations - Lu Zhang; Shilong Lei; Rong Qian; Raúl Ochoa-Hueso; Xiangtao Wang; Jie Wang; Lirong Liao; Guobin Liu; Qiang Li; Chao Zhang (Plant and Soil, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

In silico prediction of drug-induced cardiotoxicity with ensemble machine learning and structural pattern recognition - Siwen Li; Haojie Xu; Fengxi Liu; Rong Ni; Yinping Shi; Xiao Li (Molecular Diversity, 2025)

Multi-stage risk assessment and evacuation strategy for promoting urban resilience in the face of bioaerosol leakage under various meteorological information - Zhijian Liu; Yuchen He; Chenxing Hu; Rui Rong; Zhijian Dong; Chenglin Ye; Li Chen (Urban Climate, 2025)

Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Provenance and environmental changes recorded in Holocene sediments from the Southern Yellow Sea, China - Shuhuan Du; Rong Xiang; Xiang Su; Jianguo Liu; Shengfa Liu; Zirui Pan; Chuanxiu Luo; Fuchang Zhong; Li Fang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biochar supported metal cobalt activated PAA to efficiently degrade CBZ: The important role of Co (IV) in the generation of peroxyacyl radicals - Mengyu Li; Shaochun Yuan; Yuhang Liu; Siqi Chen; Mingyang Si; Rong Liu; Bangxing Ren; Zhe Zhang; Zhen Liu (Journal of Water Process Engineering, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Assessment of fate of respiratory droplets and effectiveness of different air cleaners during outpatient consultation - Haiyang Liu; Zhijian Liu; Guangpeng Yao; Zhijian Dong; Chuan Jiang; Jingwei Liu; Rui Rong; Junzhou He; Chenxing Hu; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2025)

Rapid start-up and sustained performance of an anaerobic biofilm reactor for nitrogen removal in low C/N wastewater: Characterization and microbial community analysis of the PD/A process - Yuezhen Liang; Miao Liu; Rong Zhao; Kaiyu Hou; Xiaoqin Chen; Xiaojun Fan; Li Yu; Abuliti Abudula; Guoqing Guan; Yun Duan (Journal of Environmental Chemical Engineering, 2025)

Enhancing functional metabolites and antioxidant activity of a novel alternative kombucha-like beverage: Tailor-made symbiotic microbial consortium for apple juice fermentation - Shiqi Li; Rong Liu; Zhihuan Jing; Yaodong Guo; Zhouli Wang (Food Bioscience, 2025)

Myofibrillar protein aggregate evolution regulates interfacial adsorption behavior to maintain long-term stability of high internal phase Pickering emulsions - Jiaqi Zhao; Ruren Li; Futong Song; Mingying Du; Zhifu Liu; Liangyan Rong (Food Hydrocolloids, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Upregulation of WDR4 mediated by RBFOX2 promotes laryngeal cancer progression through the WDR4/m7G/lncRNA ZFAS1/RBFOX2 axis - Baocai Lu; Xiao Li; Wenjie Miao; Qi Liu; Ruixue Li; Can Cui; Qingzu Gao; Rong Lian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nrf2 Ameliorates Sevoflurane-Induced Cognitive Deficits in Aged Mice by Inhibiting Neuroinflammation in the Hippocampus - Junhua Li; Jinfeng Li; Yafang Liu; Chuwen Hu; Hui Xu; Dong Cao; Rong Zhang; Kun Zhang (Molecular Neurobiology, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Subseasonal Prediction Skill in the CAMS-CSM Subseasonal-to-Seasonal Forecast System - Yuhan Yan; Jingzhi Su; Boqi Liu; Libin Ma; Xinyao Rong; Bo Liu; Yanli Tang; Jian Li (Advances in Atmospheric Sciences, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Gut microbiota and serum metabolomics unveil the role of Phellinus ribis polysaccharides in improving Alzheimer's disease symptoms in senescence-accelerated mice - Zhiyuan Zhang; Shuai Wang; Rong Rong; Guoying Zhang; Zheng Li; Yuanyuan Li; Rongxiang Wang; Yuhong Liu; Kejian Li (Metabolic Brain Disease, 2025)

Aloe gel polysaccharides and ascorbic acid promote collagen synthesis in mirror carp (Cyprinus carpio var. specularis) - Rong Zhang; Xiaowen Wang; Lili Liu; Huijuan Li; Hua Zhu (Aquaculture, 2025)

Genomic and antimicrobial resistance profiles of Clostridium perfringens isolated from pets in China - Mingjin Fang; Yuan Yuan; Xin Tian; Ying Liu; Ke Wu; Yanyan Zhu; Likun Zhang; Edward M. Fox; Ruichao Li; Li Bai; Menghan Li; Guerrino Macori; et al. (Veterinary Microbiology, 2025)

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Optimization strategy for Cr(VI) removal in coke-based modular constructed wetlands: A comprehensive analysis of purification efficiency, removal mechanisms, and practical feasibility - Xinlu Xiao; Xuhao Li; Xiangling Zhang; Chen Wang; Xiaoting Liu; Jing Bai; Rong Zhang; Shilong Cao; Jiezhou Hu; Zhenchao Liu; Jun Shen (Journal of Environmental Management, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Microbial interactions between Lactoplantibacillus plantarum and Rhodotorula mucilaginosa in the fermented fish juice system - Xiayin Ma; Bingqian Zhou; Lina Jiang; Mingyang Xie; Zhixing Rong; Shixian Yin; Faxiang Wang; Yongle Liu; Xianghong Li (Food Research International, 2025)

Unravelling degradation mechanisms of anion exchange membrane direct ammonia fuel cells via distribution of relaxation times - Wenzhi Li; Qing Wang; Yun Liu; Lizhen Wu; Zhefei Pan; Rong Chen; Liang An (Chemical Engineering Journal, 2025)

A chondroinductive peptide sustained-release platform design for cartilage regeneration after microfracture based on novel biomimetic recombinant protein film - Yukun Du; Yinhuan Xia; Shuang Wang; Jianyi Li; Guodong Zhang; Shuqing Chen; Xiaofan Du; Chongmin Ren; Rong-Chang Zeng; Yongming Xi; Weizhi Liu (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Experimental study on mechanical behavior of basalt under different freeze–thaw conditions - Bowen Li; Ruotao Liu; Qinyan Qiu; Huqi Zhang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

Dual-mode sensing platform based on an iodide ion synergistic covalent triazine frameworks (CTFs) for point-of-care testing (POCT) of acetylcholinesterase - Yanyue Chen; Huan Cheng; Hongling Tao; Jiali Liu; Yulong Li; Qiu-Xia Li; Tong Yang; Shuang Meng; Yunhui Yang; Rong Hu (Analytica Chimica Acta, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

First report of Colletotrichum siamense causing anthracnose on Evodia rutaecarpa in Hunan, China - Mengshan Sun; Jin Xie; Liu Cai; Rong Song; Li Zhou (Journal of Plant Pathology, 2025)

Potential role of Mc3r and Mc4r in ovarian metabolism and development in female red crucian carp (Carassius auratus red var.) - Faxian Yu; Lu Huang; Xinxin Yu; Shuxin Zhang; Shengnan Li; Rong Zhou; Wenjing Tao; Lanying Yang; Min Tao; Qizhi Liu; Shaojun Liu (Aquaculture, 2025)

Monitoring-based analysis of the responses of upper structure and tunnel lining during shield tunneling with pile cutting - Zhi-Xiong Liu; Xiao-Wei Ye; Ke Song; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Investigation into the reaction mechanism for enhanced peracetic acid catalytic decomposition by coexisting hydrogen peroxide under electrochemical conditions - Siqi Chen; Zhen Liu; Mengyu Li; Bangxing Ren; Rong Liu; Chuanliang Zhao; Yuhang Liu; Zhe Zhang; Xiaodi Duan; Yao Chen (Process Safety and Environmental Protection, 2025)

Three new maaliane-type sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Sheng-Run Guo; Hou Zhu; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry Letters, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Steam-activated biochar for efficient removal of sulfamethoxazole from water: Activation temperature-mediated differences - Shaowen Rong; Yuge He; Liangmeng Ni; Qi Gao; Xin Feng; Shushu Liu; Yanhang Zhong; Yuguo Li; Zhijia Liu (Journal of Water Process Engineering, 2025)

Environmental determinants of spatial-temporal variability in ammonia oxidizing microorganisms across diverse Chinese agricultural soils - Aiju Liu; Fangxu Rong; Guizhen Wang; Guoqin Hou; Jing Liu; Mingyue Li; Kai Liu; Zafran Gul Wazir; Hongliang Liu; Yuzhi Xu (Journal of Environmental Management, 2025)

Precipitation changes reshape desert soil microbial community assembly and potential functions - Kai Sun; Rong Yang; Jiliang Liu; Wenzhi Zhao; Xiaojun Li; Yongzhen Wang; Shujun Song (Environmental Research, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Non-uniform error correction for daily precipitation forecasting in Eastern China on the S2S model - Rong Ai; Ruoyu Liu; Chenwei Yao; Tongwen Wu; Qingquan Li; Guolin Feng; Zhiqiang Gong (Atmospheric Research, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Assessment of Geostationary Satellite Cloud Effective Radius over East China with In Situ Aircraft Measurements - Qiuli Zhang; Chao Liu; Rong Zhang; Jing Yang; Junxia Li; Bo Li; Feng Lu; Yan Yin; Hongchun Jin (Journal of Meteorological Research, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

A multi-task model for mill load parameter prediction using physical information and domain adaptation: Validation with laboratory ball mill - Yiwen Liu; Gaowei Yan; Shuyi Xiao; Fang Wang; Rong Li; Yusong Pang (Minerals Engineering, 2025)

Reticulophagy promotes EMT-induced fibrosis in offspring’s lung tissue after maternal exposure to carbon black nanoparticles during gestation by a m5C-dependent manner - Zhe Du; Qingping Liu; Mengruo Wang; Yifu Gao; Qi Li; Yizhe Yang; Tianyu Lu; Lei Bao; Yaxian Pang; Haijun Wang; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2025)

Deciphering the antibiotic resistome in stratified source water reservoirs in China: Distribution, risk, and ecological drive - Honghong Guo; Rong Li; Yuhang Su; Shuhong Xue; Na Li; Fan Chen; Xuanzi Zhangsun; Haihan Zhang; Xiaoyan Liu; Tinglin Huang (Journal of Hazardous Materials, 2025)

Development of QuEChERS based on the Z-Sep+and DLLME method for analysis of PBDEs in chicken eggs by GC–MS/MS - Xiaojing Li; Rong Yang; Zhijun Bai; Pingsheng Gan; Tao Zeng; Miao Liu; Jun Yuan (Food Chemistry, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Vitamin C alleviates intestinal damage induced by 17α-methyltestosterone in Carassius auratus - Haiyan Zhao; Tongyao Li; Chenyang Li; Zijun Xiong; Weiya Rong; Lu Cao; Gen Chen; Qing Liu; Yu Liu; Xianzong Wang; Shaozhen Liu (Aquatic Toxicology, 2025)

Identification and differential expression analysis of microRNAs in the liver and spleen tissues of Yunnan Zebu and Holstein cattle - Rong Liu; Hesong Liu; Rong Li; Chunqing Li; Heng Xiao; Shanyuan Chen (Tropical Animal Health and Production, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Integrating spatial transcriptomics and single-nucleus RNA-seq revealed the specific inhibitory effects of TGF-β on intramuscular fat deposition - Xiaoyu Wang; Chuchu Chen; Chenggan Li; Xiaochang Chen; Rong Xu; Meilin Chen; Yongpeng Li; Yihao Liu; Xiaohong Liu; Yaosheng Chen; Delin Mo (Science China Life Sciences, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Leukemia inhibitory factor promotes growth and maintains stemness in giant panda MSCs - Feiping Li; Yuliang Liu; Mengshi Zhang; Shenfei Wang; Xianbiao Hu; Xiangyu Liu; Rong Hou; Kailai Cai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Numerical evaluation on spray cooling to mitigate heat stress in cattle using computational fluid dynamics - Ruimin Yang; Wenqi Zhang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kai Liu; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2025)

Effects of microclimatic conditions and urban building configurations on aerodynamic characteristics and health risks of bioaerosols: Insights from idealized urban models - Zhijian Dong; Zhijian Liu; Chenxing Hu; Chenglin Ye; Yongjun Jin; Haiyang Liu; Rui Rong; Yuchen He; Li Chen; Chuanchen Li; Yaolong Shi; Yufeng Su (Sustainable Cities and Society, 2025)

Climate change enhances greening while human activities accelerate degradation in northern China's grasslands - Feifei Cao; Leizhen Liu; Yuping Rong; Nan Jiang; Lin Zhao; Qian Zhang; Zhitao Wu; Wenhui Zhao; Sheng Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Severity and risk to inhalation of pathogen-laden aerosol in large public spaces: Insights from fangcang shelter hospitals under multi-location release - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jingwei Liu (Journal of Hazardous Materials, 2025)

Insights into the stability assessment and reaction mechanisms of Mn-oxide-containing adsorbents for As(Ⅲ) removal in filter columns: Migration laws and stabilization mechanisms of Mn element - Rong Liu; Kun Wu; Xuan Sun; Yucheng Liu; Yuchen Wang; Jiacheng Liu; Zhihua Li (Journal of Hazardous Materials, 2025)

Analysis of genetic diversity and population structure of Pinellia ternata using EST-SSR markers - Mingxing Wang; Rong Xu; Ming Luo; Xinyao Li; Lu Wei; Mi Lei; Dahui Liu; Yuhuan Miao (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Rational screening of metal single-atom-doped ZSM-5 to promote ring-opening cracking of cycloalkanes to light olefins - Jiarong Lu; Qi Shen; Rong Fan; Guoliang Li; Yaqian Li; Xinyang Zhang; Hao Yan; Yibin Liu; Tao Liu; Xiaobo Chen (Fuel, 2025)

Examining the effects of processing techniques on the quality of hawk tea through liquid chromatography–tandem mass spectrometry and two-dimensional gas chromatography–time-of-flight mass spectrometry - Gong Feng; Jiacheng Li; Jun Liu; Rong Tan (Food Chemistry, 2025)

Using multi-modal spectroscopy technology and microscopic analysis to explore the regulation of ultra-high pressure heat-assisted treatment on the texture of ready-to-eat shrimp during storage - Na Li; Zhifeng Tan; Ruida Ma; Yafang Song; Rong Liu; Jiaxin Zhao; Ningbo Qin; Yahong Li; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Fluorescent hydrogel-based information storage materials based on dual coding of time and temperature - Kangan Hao; Runhao Yu; Mengping Xu; Rong Li; Chuan Liu; Anrong Huang; Chong Wu; Xiaoling Zuo (Chemical Engineering Journal, 2025)

Revisiting bipolar membrane electrodialysis for the production of monoprotic organic acids with different p K a and Mw - Rong Zhou; Zhiguo Dong; Xixi Ma; Lili Xue; Jinxin Liu; Jinfeng He; Weiwei Li; Li Sun; Chuanrun Li; Haiyang Yan (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

Precipitation addition during growing and non-growing seasons interactively affects the abundance of soil nematode communities in a semi-arid steppe - Yaning Li; Jingwei Guo; Xun Wang; Taohui Lian; Rong Yuan; Jiarui Feng; Cancan Zhao; Renhui Miao; Yinzhan Liu (CATENA, 2025)

Wind tunnel experiments on bioaerosol dispersion and exposure risk assessment in wastewater treatment plants under natural ventilation - Zhijian Liu; Chuanchen Li; Chenxing Hu; Rui Rong; Yaolong Shi; Zhijian Dong; Chenglin Ye; Chuang Zhang (Building and Environment, 2025)

Advancing treatment strategies against MRSA: unveiling the potency of tubuloside A in targeting sortase A and mitigating pathogenicity - Yangming Xu; Yanhe Luan; Rong Wang; Zhengjie Su; Li Wang; Yinghui Liu; Guangzhi Jiang; Bingmei Wang (World Journal of Microbiology and Biotechnology, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Feeding on different hosts displays different hemolymph protein compositions in Haemaphysalis qinghaiensis tick - Rong Cheng; Yong Li; Tian-yin Cheng; Lei Liu (Experimental and Applied Acarology, 2025)

Knowledge-based phosphorus input levels control the link between soil microbial diversity and ecosystem functions in paddy fields - Qiaorong Li; Yao Liu; Ning Su; Chang Tian; Yuping Zhang; Lin Tan; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Agriculture, Ecosystems & Environment, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Susceptibility and risk to inhalation of pathogen-laden aerosol in large public spaces: Evidence from Fangcang Shelter Hospitals under multiple ventilation rates - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jiaqi Chu; Jingwei Liu (Sustainable Cities and Society, 2025)

Migration and risk assessment of heavy metals from swine manure in an organic fertilizer - soil - ryegrass - rex rabbit system: Based on field trials - Xiaoxia Hao; Kai Liu; Li Zhu; Li Rong; Dongmei Jiang; Lin Bai (Science of The Total Environment, 2025)

The key pathogenic factor GcSP2 of Geotrichum citri-aurantii plays an important role in disrupting citrus metabolism and immunity - Rong Liu; Haoxiang Zheng; Di Wang; Haijue Zhang; Yan Wu; Xue Li; Zhengfeng Liu; QingJun Kong; Xueyan Ren (Postharvest Biology and Technology, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Min Tan; Li-Zhong Wang; Jun-Jie Hao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Investigating the matrix effect of high/low methoxyl pectins on typical aroma of apple juice using HS-SPME-GC–MS and NMR analysis - Wan Qing Li; Hui Liu; Yu Rong Guo; Xiao Yu Wang; Peng Tao Zhao (Food Chemistry, 2025)

Effects of exposure to 17α-methyltestosterone on hepatic lipid metabolism in Gobiocypris rarus - Tongyao Li; Zijun Xiong; Weiya Rong; Qiong Yang; Yue Chen; Haiyan Zhao; Qing Liu; Jing Song; Weiwei Wang; Yu Liu; Xianzong Wang; Shaozhen Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Enhanced performance and stability of sulfite/sulfide-assisted photocatalytic fuel cell with CdS@TNTs/Ti mesh photoanode - Yuxin Liu; Youxu Yu; Jinwang Li; Xun Zhu; Dingding Ye; Yang Yang; Zhefei Pan; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Weavable composite filament for sustained electricity generation from multiple sources - Rong Liu; Haoyu Li; Zhenzhou Fu; Hailou Wang; Jiamu Dai; Kai Dong; Ick Soo Kim; Wei Zhang (Chemical Engineering Journal, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Evaluation of metagenomic next-generation sequencing (mNGS) combined with quantitative PCR: cutting-edge methods for rapid diagnosis of non-invasive fungal rhinosinusitis - Xiao Liu; Shaoqin Zhou; Rong Yan; Caifeng Xia; Ruoning Xue; Zhe Wan; Ruoyu Li; Sybren de Hoog; Sarah A. Ahmed; Quangui Wang; Yinggai Song (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Pseudomonas chlororaphis ZH2: Evaluation of the Biocontrol Potential of Continuous Cropping Obstacles on the Basis of Genome Analysis, Autotoxic Substance Degradation and In Vitro Antifungal Activity - Rong Xiao; Chunfen Zhang; Shu Deng; Ciqiong Niu; Quan Li; Junjie Sun; Juantao Liu; Jianping Wang (Current Microbiology, 2025)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part II: Madden–Julian oscillation - Zhen Fu; Yi Zhang; Xiaohan Li; Congwen Zhu; Hongbo Liu; Xinyao Rong; Chengming Li (Climate Dynamics, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.